Yield of Jatropha curcas L. accessions of West Nusa Tenggara during five a year production cycle on a degraded agricultural land - Santoso, B B; Purwoko, B S; Jaya, I K D (Journal of Degraded and Mining Lands Management, 2014)
Competition between food crops and bioenergy crops in using agricultural lands should be avoided. Bioenergy crops such as Jatropha, should be grown on underutilized or degraded agricultural lands only to improve the land productivity and land coverage. Yield potential of five Jatropha curcas L. accessions of West Nusa Tenggara, Indonesia was evaluated on a degraded agriculture land at district of Kayangan, North Lombok, Indonesia. The experiment was conducted using a Randomized Complete Block Design with three blocks, and 24 plants per plot of each accession for five years. Yield components showed significant differences among accessions. Better yield performance was showed by West Lombok, Sumbawa, and Bima accessions e.g. 6.004 kg/ha, 5.885 kg/haand 5.548 kg/haat five years of age respectively. However, the yearly yield improvement was reduced after the plant reached three years of age and it was not followed by a geometrical progression based on dichotomy brancing system of the Jatropha. The high yielding accessions have a good potential to be grown on degraded agricultural lands to produce bioenergy as well as to reduce soil erosion.